“Inbursts of Maggyer”: Joyce, the Fall, and the Magyar Language - Mecsnóber, Tekla (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Samuel Beckett is alleged to have said ofJoyce that “[f]or him, there was no difference between the fall of a bomb and the fall of a leaf’ (qtd. in Cioran 33). Certainly, a fascination with the very idea of the “fall” could explain the fact that Joyce’s writings seem to contain falls and resurrections in a great variety offorms. This is a well-known feature of, for instance, Finnegans Wake, but one can also trace back the presence of a similar, ifless conspicuous, reliance on such motifs to the writer’s earlier works. What this essay attempts to propose, however, is the perhaps less obvious claim that Joyce appears to have found important—although admittedly somewhat elusive—contributions to his development of the themes of “fall” and “resurrection” in various aspects of as unlikely a source as the Hungarian language.